2007
DOI: 10.1016/j.jmb.2007.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Trans Cooperativity by a Split DNA Recombinase: The Central and Catalytic Domains of Bacteriophage Lambda Integrase Cooperate in Cleaving DNA Substrates When the Two Domains Are not Covalently Linked

Abstract: Site-specific recombinases of the lambda-integrase family recognize and cleave their cognate DNA sites through cooperative binding to opposite sides of the DNA substrate by a C-terminal catalytic domain and a flexibly linked "core-binding" domain; regulation of this cleavage is achieved via the formation of higher-order complexes. We report that the core-binding domain of lambda-integrase is able to stimulate the activity of the catalytic domain even when the two domains are not linked. This trans stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As a ligand, a 15-base-pair cognate DNA duplex, 5 0 -d(GCT CAA GTT AGT ACG)-3 0 , and its complement were used. Oligonucleotide preparation, protein expression and purification were performed using methods described previously (Subramaniam et al, 2003(Subramaniam et al, , 2007Kamadurai et al, 2003). The Int CB -DNA complex was assembled in 25 mM Tris pH 8.5 and 10 mM sodium chloride (assembly buffer) at a final protein concentration of 0.6 mM with a 10% stoichiometric excess of DNA or at an equimolar concentration of 1.75 mM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a ligand, a 15-base-pair cognate DNA duplex, 5 0 -d(GCT CAA GTT AGT ACG)-3 0 , and its complement were used. Oligonucleotide preparation, protein expression and purification were performed using methods described previously (Subramaniam et al, 2003(Subramaniam et al, , 2007Kamadurai et al, 2003). The Int CB -DNA complex was assembled in 25 mM Tris pH 8.5 and 10 mM sodium chloride (assembly buffer) at a final protein concentration of 0.6 mM with a 10% stoichiometric excess of DNA or at an equimolar concentration of 1.75 mM.…”
Section: Methodsmentioning
confidence: 99%
“…These crystal structures show that Int CB and Int Cat bind to opposite faces of the recognition sequence by adopting a clamp-like architecture with an extended linker connecting the two domains. Experiments in our laboratory with isolated protein constructs of Int CB and Int Cat showed that Int CB contributes to an increase in DNA cleavage by Int Cat even when they are not covalently linked together (Subramaniam et al, 2007). We proposed that Int CB might render the substrate DNA more suitable for cleavage by Int Cat by inducing structural changes in the DNA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding suggests that the role of Int CB is not limited to anchoring Int Cat near the site of cleavage, but also promotes DNA cleavage through some other mechanism. The observed boost in DNA cleavage in the presence of Int CB does not appear to be due to direct Int CB -Int Cat interactions since crystallographic studies with the Int CB+Cat construct do not reveal significant interdomain contacts (9), nor do NMR studies reveal any large perturbations in the conformation of Int Cat due to the presence of Int CB (14). Importantly, the stimulation of DNA cleavage by Int CB can be selectively abolished through changes in the substrate DNA sequence without affecting the basal DNA cleavage activity by Int Cat , suggesting a role for the substrate DNA in the Int CB -promoted DNA cleavage activity (14).…”
mentioning
confidence: 93%
“…If the enhancement of Int Cat by Int CB were adequately described by the chelate effect, one would expect that the cooperative effects would be lost if the two domains were separated. However, DNA cleavage assays with isolated Int Cat and Int CB constructs show that Int CB is able to increase the cleavage activity of Int Cat even when they are not expressed together as a single protein constructsthat is, when provided in trans (14). This finding suggests that the role of Int CB is not limited to anchoring Int Cat near the site of cleavage, but also promotes DNA cleavage through some other mechanism.…”
mentioning
confidence: 99%